FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU WIRAUSAHA MOMPRENEUR (STUDI KASUS : KOMUNITAS BUNDA ONLINE) - Arifah Qurrotu Aina; Heny Kuswanti Suwarsinah; Burhanuddin Burhanuddin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2018)
Rapid development of mompreneur in Indonesia become economic potential. Join the community to become one of the characteristics that can strengthen the mompreneur in running the business Komunitas Bunda Online (KBO) is one of the active community of mompreneurs who provide support to their members. The purpose of this study to determine what factors affect the entrepreneurial behavior of mompreneurs, especially those who join the community The sample in this study were 41 respondents, selected using judgment sampling technique that is based on the criteria of owning a business and having at least one child. This study analyzes the influence of individual factors and external factors on entrepreneurial behavior with the approach of Partial Least Square (PLS). The result shows that the individual factor that has the most positive effect on the behavior is the achievement desire. External factors proved to positively affect the behavior in which the growth of e-commerce in Indonesia gives a strong influence.